Immediate feedback in gamified online Chinese vocabulary quizzing: Effects on perceived cognitive load and strategic vocabulary learning - Song, Yan; Petsangsri, Sirirat; Rattana-Olan, Thanin; Cui, Jianming (Edelweiss Applied Science and Technology, 2026)
Online Chinese-as-a-second-language (CSL) learners often experience substantial cognitive demands during vocabulary study because they must rapidly encode and retrieve unfamiliar form–meaning mappings under constrained working-memory resources. Gamified quizzing platforms (e.g., Quizizz) commonly provide immediate feedback (verification plus brief explanatory feedback), yet evidence remains limited regarding how this feature shapes learners' perceived cognitive load and vocabulary learning strategy use in online CSL contexts. This randomized study investigated whether embedding immediate feedback into weekly online Chinese vocabulary quizzes over a six-week HSK preparation course reduces learners' perceived task workload and increases their strategic vocabulary learning. Sixty undergraduates were sampled using gender-stratified procedures and allocated by block randomization to Immediate Feedback, Leaderboards, or non-gamified Control conditions (n=20 per condition). Following each weekly quiz, participants completed the NASA Task Load Index (NASA-TLX) and an adapted Vocabulary Learning Strategies Questionnaire. Participant-level composite scores were analyzed using path-analytic regression with dummy-coded conditions (control as the reference). Immediate feedback significantly reduced perceived cognitive load (β=−0.42, SE = 0.08, t = −5.25, p < .001) and significantly increased reported strategy use (β=0.55, SE=0.07, t=7.86, p < .001). Interview themes aligned with the quantitative results, emphasizing uncertainty reduction, lower anxiety and frustration, increased perceived control, and more deliberate monitoring and planning when explanatory feedback was provided. These findings indicate that immediate feedback in gamified assessment can serve as a cognitively significant scaffold supporting strategic vocabulary learning during online CSL retrieval practice.